2003
DOI: 10.1080/00150190390204745
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Phase Transition in CdTiO 3 Single Crystal

Abstract: Single-crystal X-ray diffraction measurements at low temperature were carried out using the image-plate technique in the vacuum chamber at BL02B1 of SPring-8. The intensity data were collected at 20 K, 70 K, and 150 K, 36 photographs being taken at each temperature. The systematic extinctions observed at 20 K could be summarized as h = 2n + 1 for (hk0) reflections. This observation together with the observations of the ferroelectricity at this temperature uniquely determine the space group as P2 1 ma though a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…According to our calculations, the difference in lattice parameters between the paraelectric and ferroelectric phases is 0.00% for the a parameter, +0.07% for the b parameter, and −0.01% for the c parameter (relative to the Pnma structure). These results are in very good agreement with the measurements of Shan et al 18 Our calculations show that, concomitant with the slight structural change at the transition, the energy difference between the two phases is also very small. As noted in Sec.…”
Section: Phonon Behavior and Structure Of The Ferroelectric Phasesupporting
confidence: 92%
See 1 more Smart Citation
“…According to our calculations, the difference in lattice parameters between the paraelectric and ferroelectric phases is 0.00% for the a parameter, +0.07% for the b parameter, and −0.01% for the c parameter (relative to the Pnma structure). These results are in very good agreement with the measurements of Shan et al 18 Our calculations show that, concomitant with the slight structural change at the transition, the energy difference between the two phases is also very small. As noted in Sec.…”
Section: Phonon Behavior and Structure Of The Ferroelectric Phasesupporting
confidence: 92%
“…Use of polycrystalline samples has also made accurate analysis of the crystal structure difficult. 13,15,17 In an attempt to overcome these difficulties, Shan et al 18 carried out single crystal synchrotron x-ray diffraction (XRD) measurements to determine the lattice parameter changes at temperatures above and below T c to high precision. They reported that a and c parameters remained unchanged before the transition (150 K) and after the transition (70 K), while a slight contraction (0.004Å) along the b axis was detected.…”
Section: Introductionmentioning
confidence: 99%
“…The The Pmc2 1 structure of 0.72BFTM-0.28LFO (Section 3.1, Supporting Information) is adopted at low temperature by the high-pressure form of the B-site-driven CdTiO 3 ferroelectric, [9] (though more recent neutron diffraction studies have cast doubt on this [10] ), the high field form of NaNbO 3 [11] and sol-gel synthesized NaNbO 3 . [12] There are one B site and two A sites in the asymmetric unit, with the Rietveld refinement showing no indication of Bi/La cation ordering.…”
mentioning
confidence: 99%
“…Apart from these, a low-temperature ferroelectric phase is observed in Gd(Dy)FeO 3 , which arises due to the exchange striction between Gd(Dy) and Fe spins 12,13 , whereas inverse Dzyaloshinskii-Moriya interaction mechanism makes SmFeO 3 a room temperature ferroelectric 14 . Perovskite CdTiO 3 is a unique system, in which ferroelectricity is driven by a phase transition from the centrosymmetric orthorhombic structure (P bnm) to a non-centrosymmetric structure (P na2 1 ) via displacement of Ti and O ions, even though overall orthorhombic symmetry is maintained 15,16 . Recently, a new mechanism is proposed where the rotation of O octahedra coupled with lattice distortion leads to a ferroelectric phase [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%